2005
DOI: 10.1152/ajpregu.00448.2004
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids increase osmotic water permeability (Pf) of neonatal rabbit renal brush border membrane vesicles

Abstract: Glucocorticoids increase osmotic water permeability (P f ) of neonatal rabbit renal brush border membrane vesicles. there is an increase in renal brush border membrane vesicle (BBMV) osmotic water permeability and a parallel increase in aquaporin-1 (AQP1) protein abundance. The mechanisms responsible for these changes remain unknown. Because serum glucocorticoid levels rise postnatally and have previously been linked to other maturational changes in renal function, we examined the effects of glucocorticoids on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
10
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…Blunted synthesis in the medullary and cortical collecting tubule [352] The postnatal increase in glucocorticoids is a likely factor in mediating the above noted maturational changes in water permeability and aquaporin 1 expression. Administration of glucocorticoids to neonatal rabbits resulted in an increase in brush border membrane water permeability and aquaporin 1 expression [226]. Of interest, the developmental increase in thyroid hormone was not shown to be a factor mediating these postnatal maturational changes in water transport [227].…”
Section: Developmental Features Of Proximal Tubule Water Transportmentioning
confidence: 99%
See 1 more Smart Citation
“…Blunted synthesis in the medullary and cortical collecting tubule [352] The postnatal increase in glucocorticoids is a likely factor in mediating the above noted maturational changes in water permeability and aquaporin 1 expression. Administration of glucocorticoids to neonatal rabbits resulted in an increase in brush border membrane water permeability and aquaporin 1 expression [226]. Of interest, the developmental increase in thyroid hormone was not shown to be a factor mediating these postnatal maturational changes in water transport [227].…”
Section: Developmental Features Of Proximal Tubule Water Transportmentioning
confidence: 99%
“…Direct measurements of water permeability have demonstrated that the neonatal rabbit proximal tubule has a higher water permeability than that of the adult [222]. To determine the mechanism for the higher water permeability in neonatal rabbit tubules, studies were performed examining the water permeability of apical and basolateral membrane vesicles [223][224][225]. Despite the higher transepithelial water permeability, the water permeability of the apical and basolateral membrane was lower in the neonate than the adult and there was less aquaporin 1 expression on both the apical and basolateral membranes of the proximal tubule of the neonate [224,225].…”
Section: Developmental Features Of Proximal Tubule Water Transportmentioning
confidence: 99%
“…In subsequent studies, we have directly measured the neonatal and adult BBMV fluidity using the fluorophore, laurdan [20,21]. These results indicate that the membrane fluidity of the neonatal renal BBMV is indeed higher than the adult BBMV.…”
mentioning
confidence: 93%
“…14 C-n-butanol and 3 H-water were placed in the perfusion solution to measure n-butanol permeability (P DNB ) and diffusional water permeability (P DW ) simultaneously. Reproduced with permission from reference [21] The last component of the transepithelial pathway to be examined was the paracellular pathway. This component is difficult to examine directly so indirect methods were employed.…”
mentioning
confidence: 99%
See 1 more Smart Citation